2020
DOI: 10.1016/j.hemonc.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical stem cell transplant with post-transplantation cyclophosphamide and mini-dose methotrexate in children

Abstract: Background: Haploidentical stem cell transplantation (haplo-SCT) is an option for patients without human leukocyte antigen-matched related or unrelated donor. Post-transplantation cyclophosphamide (PTCy) is an effective method of graft versus host disease (GVHD) prophylaxis and permits the use of T-cell replete grafts in settings were ex vivo manipulation is not feasible. Methods: A retrospective study among patients younger than 18 years, with a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
12
2
Order By: Relevance
“…Reviewing the literature, however, some trends can be observed (see Table 2 for a summary) (9,12,14,35,41,60,74,75,78,79,95,(99)(100)(101)(102)(103). Generally, the cumulative incidence rates of severe (grade III-IV) aGvHD and overall as well as extensive cGvHD are higher in patients treated with the PTCy platform compared with those treated with ex vivo TCD (Table 1) (35,95).…”
Section: Graft-vs-host Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the literature, however, some trends can be observed (see Table 2 for a summary) (9,12,14,35,41,60,74,75,78,79,95,(99)(100)(101)(102)(103). Generally, the cumulative incidence rates of severe (grade III-IV) aGvHD and overall as well as extensive cGvHD are higher in patients treated with the PTCy platform compared with those treated with ex vivo TCD (Table 1) (35,95).…”
Section: Graft-vs-host Diseasementioning
confidence: 99%
“…Other publications report varied incidences of relapse after transplantation (between 23 and 45%), but all of these studies included multiple types of haematological malignancy and had very few ALL patients transplanted using PTCy (75)(76)(77)(78).…”
Section: Relapse and Survivalmentioning
confidence: 99%
“…Bluetters et al demonstrated complete immune reconstitution in three patients with ADA deficiency in whom cytoreductive conditioning was used with haploidentical transplant 26 . Fischer et al published a series of cases with eight patients with SCID who were taken to haploidentical HSCT, prior depletion of T lymphocytes and in whom they used cyclosporine EV for two months post‐transplant, without evidence of subsequent severe GVHD, with adequate immune recovery 27 …”
Section: Discussionmentioning
confidence: 99%
“…Patient received prophylaxis of hepatic veno‐occlusive disease with ursodeoxycholic acid and for GVHD with cyclophosphamide (50 mg/kg day + 3 and + 4), cyclosporine (to maintain levels between 200 and 300 ng/ml initiates day + 4) and methotrexate (7.5 mg/mt 2 /doses day + 5, +7, +10 and + 15) 26 . Additionally, antimicrobial prophylaxis was conducted post‐transplant with azithromycin, acyclovir, isoniazid, and caspofungin.…”
Section: Case Reportmentioning
confidence: 99%
“…The conditioning regimen was classified as myeloablative or reduced in intensity [ 22 ]. Graft-versus-host disease (GVHD) prophylaxis was performed according to the transplant type [ 23 - 25 ]. The graft was defined according to the literature [ 26 ].…”
Section: Methodsmentioning
confidence: 99%